STUDENTS PERCEPTION OF INTEGRATED EMPATHY COUNSELOR PERSONALITY IN SENIOR HIGH SCHOOL IN KEDIRI CITY: A QUALITATIVE DESCRIPTIVE STUDY - Galang Surya Gumilang (Jurnal Bikotetik (Bimbingan dan Konseling : Teori dan Praktik), 2025)
This research was conducted while becoming a field work practice supervisor at one of the senior high schools in Kediri City, some students stated that the Counselor did not have empathy as evidenced by the behavior and facial expressions of the counselor. Therefore, according to the facts in the field, the focus of the research taken was "how is the Student Perception of the Empathy Integrated Counselor Personality in high schools in Kediri City?" The research approach used a qualitative descriptive qualitative approach. With 5 students as subjects. The data collection procedure used a depth interview guide, observation guide and field documentation. The results of the study contained 3 aspects of empathy integration, namely: (1) sensitive feelings, (2) being a good listener and (3) mastery of non-verbal language. The conclusion is that the Counselor comprehensively applies empathy according to the empathy procedure. Suggestions recommended: (1) Counselors remain consistent in increasing empathy, (2) an open attitude makes students more trusting of counselors, (3) facilitating counselors in terms of empathy training, (4) further research, there are researchers who develop training related to empathy for counselors. Keywords: student perception, counselor personality, empathy